Morita equivalence of semirings with local units - Das, M.; Gupta, S.; Sardar, S.K. (Algebra and Discrete Mathematics, 2021)
In this paper we study some necessary and sufficient conditions for two semirings with local units to be Morita equivalent. Then we obtain some properties which remain invariant under Morita equivalence.